The Effects of Job Stress and Job Satisfaction on Turnover Intention - Azizah Belva Evan Syabani; Irawanto, Dodi Wirawan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Purpose – This study aims to analyze the effects of job stress and job satisfaction on the turnover intention of outsourcing employees at PT Swakarya Sinar Sejahtera. Design/Methodology/Approach – This study employs a quantitative research design using a census sampling method involving all 135 outsourcing employees. Data were collected through questionnaires and analyzed using multiple linear regression. Prior to hypothesis testing, validity and reliability tests as well as classical assumption tests (normality, multicollinearity, and heteroscedasticity) were conducted using SPSS version 25. Findings – The results indicate that job stress has a significant positive effect on turnover intention, whereas job satisfaction has a significant negative effect on turnover intention. In addition, the interaction between job stress and job satisfaction has a significant effect on turnover intention. These findings suggest that reducing job stress and enhancing job satisfaction can help lower employees’ turnover intention. Originality/Value This research provides value by simultaneously examining the effects of job stress, job satisfaction, and their interaction on turnover intention within an outsourcing context, offering evidence-based insights to support more effective employee retention strategies.